(untitled) (Revista de Estudos da Linguagem, 2024)
This study is dedicated to describing the historical development of the word family of usura (which is constituted by usura, usurar, usurário, usureiro, usurável, usurento, usuroso, usurador, zura, zuraco e usurariamente) in the Portuguese language. It takes as a basis for its diachronic and comparative approach the integration of dialectal data and online posts with a variety of other data sources in several Romance languages and in the English language. These sources constitute its corpus and the foundation which underpins the elucidation of borrowing and neology processes. It examines the etymology of this lexical family via the gradual analysis of semantic and morphological changes in each word, which is supported by textual evidence for such phenomena. Being defined from an interfacial standpoint to Morphology, Semantics, and the Lexicon, it incorporates into the resultant etymological description the discussion of themes such as word formation, the synonymy of co-radical words, affix synonymy, and morpho-lexical variation and change.